Análise comparativa das fibras colágenas e das fibras elásticas de coronárias e carótidas em pacientes autopsiados - SILVEIRA, Luciano Alves Matias da (2017)
Introduction: It is estimated that one in two deaths in developed countries is due to cardiovascular diseases. According to the Brazilian Society of Cardiology, this corresponds to approximately 300 thousand deaths per year in Brazil alone. Several lines of research are aimed at predicting cardiovascular risks, so many researchers have studied carotid arteries in an attempt to establish a correlation between carotid and coronary artery atherosclerosis. Objectives: To analyze the morphology of the carotid and coronary arteries of autopsied patients and to assess the correlation between them. Methods: After approval of the Research Ethics Committee of the Federal University of Triangulo Mineiro, sections of the right common carotid artery (RCCA), of the left common carotid artery (LCCA), of the anterior descending coronary artery (ADCA), of the posterior descending coronary artery (PDCA), and of the circumflex coronary artery (Cx) were collected from 22 autopsied patients at the Department of General Pathology. Then these sections were mounted on glass slides with Picrosirius red staining for quantification of collagen fibers and with Verhoeff’s stain for quantification of elastic fibers. Leica Qwin Plus® software was used to quantify collagen and elastic fibers. Statistical analysis was performed using Graphpad Prism® 5 software, with a significance of p<0.05. Results: Autopsy reports of 22 patients were analyzed, 59% of which were male (13) and 72.7% were white (16). The mean age was 45 years (25-74), and the mean BMI was 22.16 ± 5.51 kg/m2. After quantification of collagen fibers, the median ADCA (3.085%), PDCA (3.270%), Cx (1.9%), RCCA (2.895%) and LCCA (2.805%) of the analyzed area were obtained. The median values for quantification of elastic fibers were also obtained for ADCA (5.595%), PDCA (5.870%), Cx (5.735%), RCCA (6.195%) and LCCA (5.890%) of the analyzed area. There was a significant difference only in Picrosirius staining, between Cx and RCCA (t=2.197, p<0.05) and LCCA (t=2.212, p<0.05). There was no significant difference between the other correlations of arteries investigated (p>0.05). Conclusion: The analyses performed show that the initial process of atherosclerotic formation is common across different arteries, thus corroborating the literature, which regards it as a systemic inflammatory process affecting several arterial beds. Therefore, studies aiming to predict atherosclerotic risks must be encouraged in order to reduce the morbidity and mortality rates associated with these diseases.